Recent advances in Pichia pastoris as host for heterologous expression system for lipases : a review - Valero Barranco, Francisco (New York : Humana Press, 2018)
The production of heterologous lipases is one of the most promising strategies to increase the productivity of the bioprocesses and to reduce costs, with the final objective that more industrial lipase applications could be implemented. In this chapter, an overview of the new success in synthetic biology, with traditional molecular genetic techniques and bioprocess engineering in the last 5 years in the cell factory Pichia pastoris, the most promising host system for heterologous lipase production, is presented. The goals get on heterologous Candida antarctica, Rhizopus oryzae, and Candida rugosa lipases, three of the most common lipases used in biocatalysis, are showed. Finally, new cell factories producing heterologous lipases are presented.